Circadian rhythm perturbation causes IBS-like characteristics and altered fecal metabolome in mice - Gaichao Hong; Yajuan Zhao; Jieru Zhou; Lilin Hu; Gangping Li; Yu Jin (BMC Microbiology)
Abstract Background Circadian rhythm disturbance is associated with functional gastrointestinal disorders such as irritable bowel syndrome (IBS). This study aimed to explore the effects of dysregulated circadian rhythm on visceral sensitivity, colonic permeability, gut microbial composition, and metabolism in mice. Methods A murine model of circadian rhythm disturbance was built by performing a 6-hour phase delay. Visceral sensitivity was assessed using the abdominal withdrawal reflex score through colorectal distention. Colonic permeability was determined by measuring transepithelial resistance (TEER) and the permeability of fluorescent dextran 4 kDa. To gain insight into gut microbial composition and metabolism, 16S rRNA sequencing and untargeted metabolomics were conducted, respectively. Results Circadian rhythm disturbance led to IBS-like characteristics in mice, including visceral hypersensitivity and colonic hyperpermeability. Disrupted circadian rhythm also resulted in a decrease in intestinal microbial diversity and alterations in microbial structure. Several microbial genera were influenced by circadian rhythm disturbance, such as Bacteroides, Bifidobacterium, Desulfovibrio, Dubosiella, and Erysipelatoclostridium. Moreover, disrupted circadian rhythm altered metabolic profiles of gut microbiota and affected the levels of various metabolites, including 1-methylhistamine, nitrosylhaem, 3-aminocaproic acid, boviquinone, and carboplatin. Finally, circadian rhythm disturbance altered the relationship between microbial genera and metabolites. Conclusion Circadian rhythm disturbance contributes to visceral hypersensitivity and colonic hyperpermeability, while also altering the composition and metabolism of gut microbiota.